2016
DOI: 10.1111/hepr.12733
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis reveals an association between signal transducer and activator of transcription‐4 polymorphism and hepatocellular carcinoma risk

Abstract: A significantly increased risk of HCC associated with the rs7574865 G was found. The rs7574865 polymorphism might be used as one risk factor for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…The above results have been confirmed in these studies of Chanthra et al [24], Chen et al [32], Lu et al [33] and El Sharkawy et al [34]. Especially, Chanthra et al [24] and Zhang et al [15] pointed out G allele was a risk allele for HCC development. However, Clark et al [29], Kim et al [30] and Chen et al [32] replication result for rs7574865 showed no association with risk of HCC.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The above results have been confirmed in these studies of Chanthra et al [24], Chen et al [32], Lu et al [33] and El Sharkawy et al [34]. Especially, Chanthra et al [24] and Zhang et al [15] pointed out G allele was a risk allele for HCC development. However, Clark et al [29], Kim et al [30] and Chen et al [32] replication result for rs7574865 showed no association with risk of HCC.…”
Section: Discussionsupporting
confidence: 59%
“…Up to now, there is no STAT3 gene polymorphism meta-analysis investigating above-mentioned association. These meta-analysises about STAT4 polymorphism [14,4,15] only clarifies the relationship with risk of HCC, without chronic HBV infection, and the samples are small. Therefore, we performed a meta-analysis to evaluate the association between the two SNPs ( STAT3, STAT4 ) and HBV infection and CHB-related HCC.…”
Section: Introductionmentioning
confidence: 99%
“…STAT1 and STAT2 were demonstrated to decrease the growth capacity of HepG2 cells via increased expression stimulated by phosphatidyl-ethanolamine (56). The rs7574865 polymorphism in STAT4 was found to be a risk factor for HCC in a meta-analysis (57). Additionally, somatic mutation of JAK2 was found to be associated with a number of hematologic tumors (58,59), while gain-of-function JAK2 mutations are involved in myeloproliferative malignancies (60).…”
Section: Discussionmentioning
confidence: 99%
“…STAT4, a member of the STAT family, is an important transcription factor that regulates the expression of various molecules in vivo, and mediates cell proliferation, apoptosis, metastasis and other processes (35)(36)(37). In recent years, numerous studies have shown that single nucleotide polymorphisms of STAT4 are closely associated with the occurrence and development of liver cancer (38,39). The present study used TargetScan, PicTar, microRNA and other biological information software to predict that STAT4 may be a common target gene of miR-200a and miR-141.…”
Section: Discussionmentioning
confidence: 99%